Co-operative effect of exogenous dextranase and sodium fluoride on multispecies biofilms - Yuan-xin Qiu; Meng-ying Mao; Dan Jiang; Xiao Hong; Ying-ming Yang; Tao Hu (Elsevier, 2016)
Background/purpose: The co-operative effect of exogenous dextranase (Dex) and sodium fluoride (NaF) on Streptococcus mutans monospecies biofilms is impressive. Here we investigated the effects of the combination on a mature cariogenic multispecies biofilm and analyzed the potential mechanism. Materials and methods: A multispecies biofilm of S. mutans, Lactobacillus acidophilus, and Actinomyces viscosus was established in vitro. Dex and NaF were added separately or together. The effects of the agents on the biomass were measured. The exopolysaccharide production was determined with the scintillation counting method. The viability and morphology were evaluated using colony forming unit and confocal laser scanning microscopy, respectively. Results: In general, biofilms treated with Dex and a little concentration of NaF exhibited a lower biomass, exopolysaccharide production, and viability compared with the control group (P<0.05). Confocal laser scanning microscopy using a vital fluorescence technique showed the combination treated biofilms appeared to be loose relatively and single cells could be observed. Furthermore, the thickness and viability were also lower than either of the separate agent groups (P<0.05). Conclusion: Overall, these findings reveal that a combination of 1 U/mL Dex and 80 μg/mL NaF is a promising candidate for disrupting complex cariogenic multispecies biofilms. This feature may be in that Dex loses the structure of biofilms, thereby facilitating NaF penetration and enhancing its antibacterial effects.